Effects of Orthographic Forms on the Acquisition of Novel Spoken Words in a Second Language - Cerni, Tania; Bassetti, Bene; Masterson, Jackie (Frontiers in Communication, 2019)
The orthographic forms of words (spellings) can affect word production in speakers of second languages. This study tested whether presenting orthographic forms during L2 word learning can lead speakers to learn non-nativelike phonological forms of L2 words, as reflected in production and metalinguistic awareness. ItalianL1 learners of English as a Second Language (EnglishL2) were exposed to EnglishL2 novel spoken words (pseudowords) and real words in association with pictures either from auditory input only (Phonology group), or from both auditory and orthographic input (Phonology & Orthography group, both groups n = 24). Pseudowords and words were designed to obtain 30 semi-minimal pairs, each consisting of a word and a pseudoword that contained the same target consonant, spelled with one letter or with double letters. In Italian double consonant letters represents a long consonant, whereas the English language does not contrast short and long consonants. After the learning phase, participants performed a production task (picture naming), a metalinguistic awareness task (rhyme judgment) and a spelling task. Results showed that the Phonology & Orthography group produced the same consonant as longer in double-letter than in single-letter lexical items, while this was not the case for the Phonology group. The former group also rejected spoken rhymes that contained the same consonant spelled with a single letter in one word and double letters in the other, because they considered these as two different phonological categories. Finally, the Phonology & Orthography group learned more novel words than the Phonology group, showing that orthographic input results in more word learning, in line with previous findings from native speakers.